Deep oxidation of tetrachloromethane and hexachloroethane on the heterogeneous catalysts - Гаєвська, Т.А.; Бурлаченко, Є.С.; Красільнікова, Н.Л.; Плескун, С.М.; Іванов, С.В.; Білокопитов, Ю.В. (Proceedings of National Aviation University (archive), 2005)
The comparative research of catalytic properties of various oxides of metals in an oxidation reaction of a tetrachlormethane and hexachloroethane is conducted and is exhibited, that active and stable catalyst at oxidation chlorocarbons will be for which the processes of decomposing of chlorides on a surface dominate above their formation.